TRANSLATION OF PHRASEOLOGICAL UNITS AND ITS LEXICAL DIFFICULTIES - Khaydarova , Laylo; Isheryakova , Joanna (Innovative Development in Educational Activities, 2023)
People in different parts of the world engross themselves in different conversations and their conversation usually evolves in English language, as it ensures that everyone can participate in debates and discussions. English language considered as an international language and serves as a communication tool between parties and politicians. Although this not only one case where people can identify English language, this language is in books of well-known authors, such as, Shakespeare, Jack London and others. While reading these books in original language without turning to translation version, one can come across phraseological expressions, idioms, colloquialisms, neologisms and etc. In order to understand such kind of above-mentioned expressions, a reader should be aware of them beforehand and be able to recognize their role and function in the text. This article will discuss the main issues of translation in terms of phraseology and common specific ways of overcoming them.